Youth identity and society : the clash of the heartlands and the cosmopolitan society. - Peng Shi Yuan Damien. (2011)
Essay explores the clash of beliefs and idealogoy of the youth and their parents' generation, through the work of Colin Cheong and Dareen Shiau